Practicing recreational sports activities and their implications in enhancing the mental health of army retirees - Bouaziz, mohammed; bouzghada, nacer (sports creativity, 2025)
The study aimed at revealing what the practice of sports recreation activities adds in raising the psychological health of army retirees practicing and non-practicing sports recreation activity. The researchers used the descriptive method, with a sample of 50 retirees in the state of Relizane, and the data was collected using a psychological health scale. The results of this study revealed that practicing sports recreational activity increases the degree of mental health among army retirees, and the researchers recommended paying attention to this group by encouraging and providing appropriate conditions for practicing these activities